2015
DOI: 10.1177/1534735415607318
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Group Intervention on Enhancing Cognitive Emotion Regulation Strategies in Breast Cancer Patients

Abstract: Purpose. To evaluate the long-term effect of group intervention on enhancing cognitive emotion regulation (CER) strategies in female patients with early-stage breast cancer. Methods. The sample included 174 patients who were diagnosed with early-to-mid stage breast cancer, completed adjuvant therapy, and agreed to fill out demographic and cognitive emotion regulation questionnaires (CERQ). About half of the patients (86, 49.4%) chose to participate in an 8-session group intervention (intervention group) while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Numerous interventions that include disengagement coping as a target have been developed for both cancer and non-cancer populations (Steinhardt & Dolbier, 2008). For example, in a recent study of a group intervention designed to enhance “cognitive emotion regulation” among breast cancer patients, improvements were demonstrated in both adaptive and maladaptive coping (Hamama-Raz et al, 2016). Furthermore, specific psychotherapy approaches often utilized with cancer patients (e.g., cognitive-behavioral therapy, cognitive-behavioral stress management) attempt to target disengagement coping (e.g., through the use of behavioral activation; identifying and challenging cognitive distortions; and addressing damaging, negative core beliefs about oneself and the world).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous interventions that include disengagement coping as a target have been developed for both cancer and non-cancer populations (Steinhardt & Dolbier, 2008). For example, in a recent study of a group intervention designed to enhance “cognitive emotion regulation” among breast cancer patients, improvements were demonstrated in both adaptive and maladaptive coping (Hamama-Raz et al, 2016). Furthermore, specific psychotherapy approaches often utilized with cancer patients (e.g., cognitive-behavioral therapy, cognitive-behavioral stress management) attempt to target disengagement coping (e.g., through the use of behavioral activation; identifying and challenging cognitive distortions; and addressing damaging, negative core beliefs about oneself and the world).…”
Section: Discussionmentioning
confidence: 99%
“…Since interpersonal regulation revealed a greater and more positive impact, it might be particularly helpful for breast cancer patients to engage in regulatory processes with their most immediate social relationships (e.g., family and close friends), as long as they are willing to get involved in the sharing process. Similarly, and in line with recent research (e.g., [36]), group intervention, support groups, or even online forums also represent powerful emotion regulation tools as they provide a safe environment where breast cancer patients can express their feelings, share their thoughts and disease-related concerns, trade useful information, and learn new techniques to better manage their condition. In return, these women feel more empowered, and get the support they need to cope with the disease from people that are in similar situations.…”
Section: Discussionmentioning
confidence: 58%
“…However, as mentioned earlier, several studies on altering the general use of coping strategies in breast cancer patients have reported that the intervention participants had greater coping efficacy, lower depressive symptoms and less perceived stress [9]. Hamama-Raz et al [32] reported that appropriate interventions during cancer treatment changed the pattern of use of coping strategies and that the patients then experienced more positive long term outcomes in terms of the enhancement of positive strategies and reduction of negative coping strategies.…”
Section: Discussionmentioning
confidence: 96%